Modelling of vibration and noise control of a submerged circular plate - Jerzy Wiciak (Archives of Acoustics)
This paper presents a numerical approach for modelling of a thin circular plate clamped on the edges in a rectangular enclosure and containing distributed piezoelectric actuators under dynamic mechanical and electrical loadings. The plate is also loaded on one side by heavy fluid (water) and on the other side contacts with air. The finite element method analysis was performed, supported by the ANSYS computer package. The numerical solutions were confirmed experimentally. The obtained results demonstrate a significant reduction of the vibration level and sound pressure level with the use of piezoceramic actuators.